Obesity, International Food and Beverage Industries, and Self‐Regulation: The Fragmentation of Information Strategies. Issue 3 (September 2015) - Jensen, Jørgen Dejgård; Ronit, Karsten
<x xml:space="preserve">Abstract</x> This article explores how large international companies in the breakfast cereal, snack, and beverage industries address the issue of obesity, and how their strategies are governed by various forms of self‐regulation. In a first step, we study websites of ten companies and identify five different dimensions: (i) mission statements, (ii) educational commitment statements, (iii) nutrition labeling, (iv) marketing code of conduct, and (v) education initiatives aimed at professionals. Based on a coding of these activities, we conducted hierarchical cluster analysis and selected five case companies for in‐depth investigation. This analysis reveals different types of self‐regulation strategies, reflecting differences in levels of commitment and instrumentation. Some companies pursue defensive strategies, some with an element of "blame‐control, " whereas others adopt offensive strategies to promote their products. Differences in market communication strategies can be attributed to variations in product portfolio and market orientation, and can also be seen as attempts to forestall public regulation.